“Dialogues”: Art Exhibition Promoting Intercultural Communication and Tolerance among Nations - Gulbinaitė, Gertrūda; Senkevičiūtė, Evelina; Ulvydienė, Loreta (Respectus Philologicus, 2019)
[text in Lithuanian]
Keywords: none